2018
DOI: 10.22201/fesi.20072082.2018.11.67517
|View full text |Cite
|
Sign up to set email alerts
|

New Records of the Genus Anastrepha Schiner, 1868 (Diptera: Tephritidae) in the Isthmus of Tehuantepec, Oaxaca, Mexico

Abstract: <p>Five species of the genus <em>Anastrepha</em> Schiner are reported for the first time from the region of the Isthmus of Tehuantepec, Oaxaca. <em>A. bezzii</em> Lima, <em>A. minuta</em> Stone, <em>A. tumida</em> Stone, <em>A. furcata</em> Lima and <em>A.</em> sp. new species<em>, </em>of which last two are new records for Mexico. Some taxonomic aspects are discussed, as well as the relationship of the ecosystems present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…acris, A. leptozona, A. montei (Hernández-Ortiz, 1992); A. cordata (Hernández-Ortiz, 1999);A. bahiensis, A. bicolor, A. canalis, A. compressa, A. crebra, A. zuelaniae (Antonio-Hernández, 2006); A. bezzii, A. furcata, A. minuta, A. tumida (Antonio-Hernández et al 2018b); A. curvicauda (Norrbom et al 2018); A. sp. nueva especie, A. pastranai (en este trabajo).…”
Section: Especies Oaxacaunclassified
“…acris, A. leptozona, A. montei (Hernández-Ortiz, 1992); A. cordata (Hernández-Ortiz, 1999);A. bahiensis, A. bicolor, A. canalis, A. compressa, A. crebra, A. zuelaniae (Antonio-Hernández, 2006); A. bezzii, A. furcata, A. minuta, A. tumida (Antonio-Hernández et al 2018b); A. curvicauda (Norrbom et al 2018); A. sp. nueva especie, A. pastranai (en este trabajo).…”
Section: Especies Oaxacaunclassified
“…Previous studies reported 39 known described species of Anastrepha in Mexico [ 24 , 43 ], including recent records of Anastrepha tehuacana Norrbom [ 16 ] and Anastrepha furcata Lima [ 44 ]. For the state of Quintana Roo, there are currently 12 known species of Anastrepha [ 24 , 36 , 43 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anastrepha alveata, A. barnesi (Hernández-Ortiz, 1987); A. chiclayae, A. distincta, A. fraterculus, A. ludens, A. obliqua, A. pallens, A. robusta, A. serpentina, A. spatulata, A. striata (Aluja et al 1987); A. acris, A. leptozona, A. montei (Hernández-Ortiz, 1992); A. cordata (Hernández-Ortiz, 1999); A. bahiensis, A. bicolor, A. canalis, A. compressa, A. crebra, A. zuelaniae (Antonio-Hernández, 2006); A. bezzii, A. furcata, A. minuta, A. tumida (Antonio-Hernández et al 2018b); A. curvicauda (Norrbom et al 2018); A. sp. nueva especie, A. pastranai (en este trabajo).…”
Section: Especies Oaxacaunclassified
“…(Aluja et al 2003); en cuatro áreas del Istmo de Tehuantepec, 20 especies (Antonio-Hernández, 2006), este último dato se ha modificado sustancialmente con resultados obtenidos a partir de investigaciones posteriores realizadas en esta región. Tomando como referencia los trabajos realizados por Cancino y Pérez, (1987); Hernández-Ortiz (1992); Antonio-Hernández (2006); Antonio-Hernández y García-Ramírez, (2018b), el género Anastrepha se encuentra representado en el Istmo de Tehuantepec por las siguientes especies: A. acris, A. alveata, A. bahiensis, A. barnesi, A. bezzii, A. bicolor, A. canalis, A. chiclayae, A. compressa, A. crebra, A. curvicauda, A. distincta, A. fraterculus, A. furcata, A. leptozona, A. ludens, A. minuta, A. montei, A. obliqua, A. pallens, A. pastranai, A. robusta, A. serpentina, A. spatulata, A. striata, A. tumida, A. zuelaniae y A. sp.…”
Section: Diversidad En El Istmo De Tehuantepecunclassified